PEMBUDIDAYAAN JAMUR KUPING PADA SEBELAS JENIS KAYU - Sihati Suprapti (Jurnal Penelitian Hasil Hutan, 1988)
he  ear mushroom,   Auricularia polytrica (Basidiomycetes: Auriculariaceae)   was cultivated   on  logs of eleven  wood species,  i.e.   hamerang  (Ficus  grossularoides Burn, f.), jeungjing  (Albizia  falcataria (L.)   Fosb.),  kaliandra (Calliandra calothyrsus Meissn.),  kihuut (Vernonia  arborea   Ham.), kipiit (Maesa ramentacea Wall.), kiwates   (Eurya  acuminata AP. DC.),  manii  (Maesopsis eminii  Engl.),   sehang (Ficus  padana  Burn.  f.),   seuseureuhan   (Piper  aduncum  L.),   teureup  (Artocarpus  elastica  Reinw.)   dan  tusam  (Pinus  merkusii Jung  et de Vr.).   The logs were kept   slanted  on an angle of ± 60°  with bamboo  supports   in a mushroom  house,  at Gunung Bunder  forest  complex,  Bogor.  The mature  mushroom  were harvested daily  after  the growth  of  the fruiting  body.The  logs start  producing   fungus   two  months   after  inoculation.   The  average yield per  log during  the seven  month observation   was 412.15  g  (sehang),  302.43  g  (manii),   251.6   g  (seuseureuhan),   243.6 g  (kihuut).   The  lower  yield   was 28.85  g (kiwates),  12 g (jeungjing) and 8.85  (tusam).After seven  month  observation,  the higher total yield  was obtained  from  manii (83.18  kg),  seuseureuhan  (79.97 kg), sehang  (76.91 kg),  kihuut   (69.09 kg)  perm3 of  log. The  lower  total  yield  per m3 of  log was obtained  from  kaliandra (29.35 kg),  teureup (22.75 kg),  kiwates  (11.98 kg),  Jeungjing  (4.45kg) and the lowest  total yield  was on tusam  (1.87 kg).